2019
DOI: 10.1029/2018jg004619
|View full text |Cite
|
Sign up to set email alerts
|

Using Stable Carbon Isotopes of Seasonal Ecosystem Respiration to Determine Permafrost Carbon Loss

Abstract: High latitude warming and permafrost thaw will expose vast stores of deep soil organic carbon (SOC) to decomposition. Thaw also changes water movement causing either wetter or drier soil. The fate of deep SOC under different thaw and moisture conditions is unclear. We measured weekly growing‐season δ13C of ecosystem respiration (Recoδ13C) across thaw and moisture conditions (Shallow‐Dry; Deep‐Dry; Deep‐Wet) in a soil warming manipulation. Deep SOC loss was inferred from known δ13C signatures of plant shoot, ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 96 publications
1
19
0
Order By: Relevance
“…Microbial metabolism, on the other hand, strongly favors the lighter isotope, 12 C (Trumbore, 2006). Soil organic matter becomes more decomposed and processed with depth, and the 13 C composition (δ 13 C) of bulk soil C can increase up to 6‰ from the surface down to ~85 cm (Mauritz et al, 2019; Pries et al, 2013; Schuur et al, 2003). Stable C isotope data can be complemented by radiocarbon ( 14 C) to provide further insight on R eco source contributions.…”
Section: Introductionmentioning
confidence: 99%
“…Microbial metabolism, on the other hand, strongly favors the lighter isotope, 12 C (Trumbore, 2006). Soil organic matter becomes more decomposed and processed with depth, and the 13 C composition (δ 13 C) of bulk soil C can increase up to 6‰ from the surface down to ~85 cm (Mauritz et al, 2019; Pries et al, 2013; Schuur et al, 2003). Stable C isotope data can be complemented by radiocarbon ( 14 C) to provide further insight on R eco source contributions.…”
Section: Introductionmentioning
confidence: 99%
“…It is possible that this negative carbon isotopic shift is due to the release of methane clathrates (CH 4 ) into the atmosphere during terminal deglaciation. Furthermore, the contribution of deep soil organic carbon (SOC) loss and CH 4 from terrestrial permafrost may also have contributed to widespread δ 13 C perturbation 31 .…”
Section: Discussionmentioning
confidence: 99%
“…Tarnocai et al, 2009;Ciais et al, 2012;Schneider et al, 2013;Eggleston et al, 2016;Ganopolski and Brovkin, 2017;Treat et al, 2019). The freezing and burial of organic matter across the glacial cycle may significantly imprint the terrestrial biosphere CO2 size and δ13C signature (Tarnocai et al, 2009;Ciais et al, 2012;Schneider et al, 2013;Eggleston et al, 2016;Ganopolski and Brovkin, 2017;Mauritz et al, 2018;Treat et al, 2019). Schneider et al (2013) and Eggleston et al (2016) both observed a permanent increase in atmospheric δ13C during the last glacial cycle, of âĹij0.4‰ and attributed its cause likely due to soil storage of carbon in peatlands which were buried or frozen as permafrost as the glacial cycle progressed.…”
Section: C14mentioning
confidence: 97%
“…Printer-friendly version Discussion paper ston et al, 2016;Mauritz et al, 2018;Treat et al, 2019), and were partially or wholly replaced by other soil stocks of carbon (e.g. Lindgren et al, 2018).…”
Section: Cpdmentioning
confidence: 99%
See 1 more Smart Citation